2006
DOI: 10.1016/j.ejcts.2006.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in the tri-modality treatment of small cell lung cancer.Stage-dependent survival

Abstract: Surgical intervention is promising and warrants prospective trials to be evaluated as an important adjunct to multi-modality therapy regimen in SCLC as regards to its impact on relapse free and overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 14 publications
3
17
0
2
Order By: Relevance
“…Similar observations were reported by A. Granetznyet al 12 , with R0 resection in 90 patients (94.7%) and R1 resection in 5 patients (5.3%).…”
Section: Discussion:-supporting
confidence: 79%
See 1 more Smart Citation
“…Similar observations were reported by A. Granetznyet al 12 , with R0 resection in 90 patients (94.7%) and R1 resection in 5 patients (5.3%).…”
Section: Discussion:-supporting
confidence: 79%
“…These observations were consistent with other studies. A. Granetzny et al 12 reported a postoperative complication rate of 17% (16/95) which comprised of 6 cases of atrial fibrillation, 5 cases of atelectasis, 3 cases of pneumonia and 2 cases of wound infection. Adjuvant treatment was recorded as radiotherapy, chemotherapy, or both as appropriate.…”
Section: Discussion:-mentioning
confidence: 99%
“…These results are comparable to those obtained by Granetzky et al who showed a 5-year survival of 42% for patients with LSCLC stages I and II after operation, chemotherapy, TRT, and PCI [10]. Rea et al reported a 5-year survival of 52% for patients with stage I SCLC and of 30% for patients with stage II disease after trimodal treatment [22].…”
Section: Discussionsupporting
confidence: 78%
“…In SCC of the lung, whether surgical treatment following neoadjuvant therapy is beneficial remains unclear, because there have not been any data from prospective randomized control trials comparing chemotherapy and/or radiation with surgery after neoadjuvant therapy (12). However, according to a previous retrospective study, surgery after neoadjuvant chemotherapy can improve the prognosis of patients with clinical stage IIIA or IIIB of SCC of the lung if complete regression of mediastinal nodes has been achieved by neoadjuvant chemotherapy (13). Furthermore, in SCC of the bladder, neoadjuvant chemotherapy followed by surgery is reported to have beneficial roles for improving the patient survival (14).…”
Section: Discussionmentioning
confidence: 99%